Cost analysis of open radical cystectomy versus robot‐assisted radical cystectomy. (1st November 2017) - Bansal, Sukhchain S.; Dogra, Tara; Smith, Peter W.; Amran, Maisarah; Auluck, Ishna; Bhambra, Maninder; Sura, Manraj S.; Rowe, Edward; Koupparis, Anthony
Abstract : Objectives: To perform a cost analysis comparing the cost of robot‐assisted radical cystectomy (RARC) with open RC (ORC) in a UK tertiary referral centre and to identify the key cost drivers. Patients and Methods: Data on hospital length of stay (LOS), operative time (OT), transfusion rate, and volume and complication rate were obtained from a prospectively updated institutional database for patients undergoing RARC or ORC. A cost decision tree model was created. Sensitivity analysis was performed to find key drivers of overall cost and to find breakeven points with ORC. Monte Carlo analysis was performed to quantify the variability in the dataset. Results: One RARC procedure costs £12 449.87, or £12 106.12 if the robot was donated via charitable funds. In comparison, one ORC procedure costs £10 474.54. RARC is 18.9% more expensive than ORC. The key cost drivers were OT, LOS, and the number of cases performed per annum. Conclusion: High ongoing equipment costs remain a large barrier to the cost of RARC falling. However, minimal improvements in patient quality of life would be required to offset this difference.